(untitled) (Journal of Foreign Language Studies, 2024)
Vietnam and China have maintained a long-standing and growing cooperative relationship in many areas. In the context of the 4.0 technology era, there seems to be an increase in the number of Vietnamese learners of Chinese. These learners not only attend traditional classes but also self-study in many online platforms. This study employed a large-scale survey to examine the current use of online self-study platforms to learn Chinese in Vietnam and thence propose an idea to develop a system that can meet the needs of learners in this country. The survey results from 650 responses reveal that learners expect a system with rich repository and new features that can improve the self-study quality.